PENGARUH MEDIA PEMBELAJARAN EDUCANDY TERHADAP MINAT BELAJAR SISWA PADA PEMBELAJARAN IPAS KELAS V DI SD NEGERI 42 PEKANBARU - Hafizah, Indah; Marhadi, Hendri; Guslinda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of Educandy learning media on student learning interest in Science and Natural Sciences (IPAS) subjects for fifth grade students at SD Negeri 42 Pekanbaru. The research employed a quantitative approach with a quasi-experimental design, specifically the nonequivalent control group design. The study population consisted of 89 fifth-grade students, with a sample of 42 students divided into two groups: 22 students in class V A as the control group and 20 students in class V D as the experimental group. Data collection techniques included observation sheets and questionnaires using a four-point Likert scale covering indicators of feelings of pleasure, acceptance, interest, and student involvement. The instrument validity test used product moment correlation, while reliability testing employed Cronbach's Alpha. Data analysis included normality tests, homogeneity tests, independent sample t-tests, Pearson correlation tests, and N-Gain tests. The results showed that the experimental class experienced an average increase of 10.20 points from 62.55 to 72.75, while the control class only increased by 4.95 points from 61.68 to 66.63. The independent sample t-test produced a significance value of 0.001, smaller than 0.05, indicating that Ha was accepted and Ho was rejected. The N-Gain test showed a score of 0.513 in the moderate category for the experimental class and 0.191 in the low category for the control class. These findings prove that Educandy learning media has a significant influence on increasing student learning interest in IPAS learning at SD Negeri 42 Pekanbaru through interactive and engaging learning experiences.